Novel control of cardiac myofilament response to calcium by S-glutathionylation at specific sites of myosin binding protein C - Patel, Bindiya G.; Wilder, Tanganyika; Solaro, R. J. (Frontiers in Physiology, 2013)
Our previous studies demonstrated a relation between glutathionylation of cardiac myosin binding protein C and diastolic dysfunction in a hypertensive mouse model stressed by treatment with salt, deoxycorticosterone acetate, and unilateral nephrectomy. Although these results strongly indicated an important role for S-glutathionylation of myosin binding protein C as a modifier of myofilament function, indirect effects of other post-translational modifications may have occurred. Moreover, we did not determine the sites of thiol modification by glutathionylation. To address these issues, we developed an in vitro method to mimic the in situ S-glutathionylation of myofilament proteins and determined direct functional effects and sites of oxidative modification employing Western blotting and mass spectrometry. We induced glutathionylation in vitro by treatment of isolated myofibrils and detergent extracted fiber bundles (skinned fibers) with oxidized glutathione (GSSG). Immuno-blotting results revealed increased glutathionylation with GSSG treatment of a protein band around 140 kDa. Using tandem mass spectrometry, we identified the 140 kDa band as cardiac myosin binding protein C and determined the sites of glutathionylation to be at cysteines 655, 479, and 627. Determination of the relation between Ca2+-activation of myofibrillar acto-myosin ATPase rate demonstrated an increased Ca2+-sensitivity induced by the S-glutathionylation. Force generating skinned fiber bundles also showed an increase in Ca-sensitivity when treated with oxidized glutathione, which was reversed with the reducing agent, dithiothreitol. Our data demonstrate that a specific and direct effect of S-glutathionylation of myosin binding protein C is a significant increase in myofilament Ca2+-sensitivity. Our data also provide new insights into the functional significance of oxidative modification of myosin binding protein C and the potential role of domains not previously considered to be func